Numerosities are not ersatz numbers. (15th December 2021) - Dutilh Novaes, Catarina; dos Santos, César Frederico
Abstract: In describing numerosity as "a kind of ersatz number, " Clarke and Beck fail to consider a familiar and compelling definition of numerosity, which conceptualizes numerosity as the cognitive counterpart of the mathematical concept of cardinality; numerosity is the magnitude, whereas number is a scale through which numerosity/cardinality is measured. We argue that these distinctions should be considered.